Developing Nearpod-Based Interactive Multimedia on the Topic of Indonesian Cultural Diversity for 4th Grade Elementary School Students - Alawiyah, Indi Azza; Ahmadi, Farid (Journal of Integrated Elementary Education, 2024)
This research aims to create a valid, practical, and effective Nearpod-based interactive learning media to improve learning outcomes of social sciences content on the material "Indonesian Cultural Diversity." This is development research with the ADDIE model (analysis, design, development, implementation, and evaluation). Based on the results of the expert assessment, the validity of the product obtained a score of 92.18% with the criteria of "very valid" in the aspects of suitability of material and learning objectives, language, media display, excellence, and media use. Material validation scores on aspects of accuracy with learning objectives, students' level of thinking, language, and supporting aspects (videos, images, quizzes) also fall into the "very valid" category with a score of 95%. Based on student responses to the content of the material, ease of use, material display, linguistic aspects, and readability of the material are also in the very valid category, with a percentage of 91%. Based on the N-Gain calculation of students' pretests and post-tests, Nearpod media received a score of 0.74 from 22 large group students, while six small group students obtained a score of 0.8 in the "High" category, as well as the material achievement score from the N-Gain results of 92.3% with the "Very Good" category, which means that 26 out of 28 students get scores above learning objective completeness criteria (KKTP).